The Effect of Coordination and Supervision on the Performance of Fisheries Extension Officers at the Cirebon City Food Security, Agriculture and Fisheries Service - Akmad Sutrisno; Ida Rosnidah; Hery Nariyah (ijd-demos, 2022)
The objectives of this study are (1) the magnitude of the effect of coordination on the performance of the fishery instructor at the Cirebon City Food Security, Agriculture and Fisheries Service, (2) the magnitude of the effect of supervision on the performance of the fishery instructor at the Cirebon City Food Security, Agriculture and Fisheries Service, (3) the magnitude of the the effect of simultaneous coordination and supervision on the performance of fishery instructors at the Cirebon City Food Security, Agriculture and Fisheries Service. The method used is a quantitative approach. Data were collected through questionnaires and analyzed using multiple regression models. The results of the study: (1) coordination has a positive effect on performance, indicated by the value of sig. of 0.035 0.05, (2) supervision has a positive effect on performance, which is the value of sig. of 0.005 005, (3) coordination and supervision simultaneously affect the performance indicated by the value of sig. of 0.00 0.05.Keywords: Coordination, Supervision, Fisheries Extension Performance AbstrakTujuan penelitian ini adalah (1) besarnya pengaruh koordinasi terhadap kinerja penyuluh perikanan pada Dinas Ketahanan Pangan, Pertanian dan Perikanan Kota Cirebon, (2) besarnya pengaruh supervisi terhadap kinerja penyuluh perikanan pada Dinas Ketahanan Pangan, Pertanian dan Perikanan Kota Cirebon, (3) besarnya pengaruh koordinasi dan pengawasan secara simultan terhadap kinerja penyuluh perikanan pada Dinas Ketahanan Pangan, Pertanian dan Perikanan Kota Cirebon. Metode yang digunakan adalah pendekatan kuantitatif. Data dikumpulkan melalui kuesioner dan dianalisis menggunakan model regresi berganda. Hasil penelitian: (1) koordinasi berpengaruh positif terhadap kinerja yang ditunjukkan dengan nilai sig. sebesar 0,035 0,05, (2) supervisi berpengaruh positif terhadap kinerja yaitu nilai sig. sebesar 0,005 005, (3) koordinasi dan supervisi secara simultan berpengaruh terhadap kinerja yang ditunjukkan dengan nilai sig. dari 0,00 0,05.Kata kunci: Koordinasi, Supervisi, Kinerja Penyuluhan Perikanan